Pemanfaatan Artificial Intelligence (AI) sebagai Sistem Pendukung (Supporting System) Kegiatan Intrakurikuler di SMAN 1 Montong Gading – Lombok Timur - Untung Waluyo; Henny Soepriyanti; Eka Fitriana; La Ode Alfin Aris Munandar (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The integration of Artificial Intelligence (AI) into educational practices has become increasingly crucial in enhancing the effectiveness of teaching and learning processes. This community service aims to equip participants with practical knowledge of the application of AI as a supporting system for intracurricular activities at SMAN 1 Montong Gading, Lombok Timur. The method of community service undertaking involved an interactive workshop to introduce AI concepts and provision of ongoing post program mentoring. These sessions were designed to not only deliver theoretical knowledge but also to offer practical applications of AI in an educational context. The workshop yielded a significant increase in teachers' competence, with 96% of participants reporting a deeper understanding and confidence in using AI tools within their teaching practices. Teachers also successfully developed AI-based teaching materials, which were implemented and positively impacted classroom dynamics. The implications of this study suggested that with proper training and support, AI can be a powerful tool in personalizing education and improving student engagement. Furthermore, the program fosters a collaborative environment among educators, encouraging the sharing and refining of AI-integrated teaching practices. The study recommends continued support and regular evaluations to sustain and enhance the integration of AI in educational settings. This will potentially serve as a model for similar initiatives in other schools